2014
DOI: 10.1017/s1751731114002006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary protein level on carcass traits and meat properties of Cinta Senese pigs

Abstract: The aim of this study was to test the effect of various dietary protein contents (CP) on the carcass traits and the meat quality of Cinta Senese pigs. A total of 60 Cinta Senese pigs were equally distributed in four dietary groups that were balanced for sex (barrows and gilts) and live weight. The animals in the groups were fed one of four diets (80CP, 100CP, 130CP and 160CP) containing different CP contents (80, 100, 130 and 160 g/kg, respectively). The diets were administered to the pigs during the entire gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 32 publications
(43 reference statements)
4
17
2
Order By: Relevance
“…Despite the different dietary regimen, no modifications in weight gain, average daily gain (ADG), and backfat thickness were observed at the end of the growing phase. During the following finishing phase any parameters reached the statistical significance The observed values for ADG and backfat thickness are in line with those reposted on previous studies on Cinta Senese [19,21]. However, results on the growing phase are in contrast with those reported by several authors who, in lean genotypes, spotted a clear negative effect of protein restriction on growth performances [6,22,23,24,25].…”
Section: Resultssupporting
confidence: 88%
“…Despite the different dietary regimen, no modifications in weight gain, average daily gain (ADG), and backfat thickness were observed at the end of the growing phase. During the following finishing phase any parameters reached the statistical significance The observed values for ADG and backfat thickness are in line with those reposted on previous studies on Cinta Senese [19,21]. However, results on the growing phase are in contrast with those reported by several authors who, in lean genotypes, spotted a clear negative effect of protein restriction on growth performances [6,22,23,24,25].…”
Section: Resultssupporting
confidence: 88%
“…Currently, this knowledge is available only for Iberian pigs whose protein and energy requirements, as well as their optimal ratio, have been studied for each rearing phase [5,6,25,26]. Previous studies on Cinta Senese evaluated the whole growing-fattening period [8,9,27]. These studies highlighted the lower protein requirements of Cinta Senese compared to that of lean genotypes, whose recommended protein intake for growing pigs is 16% CP [15].…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis study, the same authors also observed that the carcass components of obese genotypes follow a different pattern of relative growth in comparison with the lean genotypes [7]. In the Cinta Senese breed, two studies were carried out, testing four diets with increasing CP contents (8%, 10%, 13% and 16%) in animals from 50 to 145 kg [8,9]. Considering both the growth performance and slaughtering traits of the whole post-weaning-fattening period, the authors stated that a content of 10% CP in the diet was adequate to fulfill Cinta Senese protein requirements.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that, as long as AA are balanced with supplementation of crystalline AA, the nutritive value of protein-restricted diet is similar to the conventional diet in terms of growth performance and body composition in pigs [12, 30, 31]. However, when the dietary CP content was reduced by 8 percentage units, the performance of growing pigs was reduced as a result of inadequate supply of nitrogen for the synthesis of dispensable AA [30].…”
Section: Discussionmentioning
confidence: 99%